Aplikasi wayarles menggunakan telefon bimbit dengan-WAP / Wan Maria Wan Osman - Wan Maria, Wan Osman (2001)
“Wireless Site Solution using WAP-enabled Mobile Phone” is an application developed based on WAP technology. It makes use of the N-tier Client/Server Architecture to provide users especially those who are still new in this technology. With wireless access to manage their daily task and get latest information as well. The main purpose of this project is to provide an alternative for users in managing their daily tasks in some simple clicks and also to allow users to access information in a very interesting way. There are two major modules in this application which are the user module and administrator module. The user module enables user to use all the services such as News, Weather Report and an interactive communication that is Chat. While the administrator module provide the facilities for database administrator to carry out the maintenance work. The administrator will have right to add new data, modify or even delete the records in the database. This application is developed using WML 1.1 and WMLScript 1.1. The platform that will be using is Windows 2000. It utilizes Microsoft Access 2000 in developing a relational database for the system. Besides that, the development tools that involves are WAP toolkit and WAP browser creating with the purpose of migrating traditional way of managing daily task to wireless platform, it is believed that the system of this nature will become important to every WAP user in the near future. This is because all the services in this application are close-to-life and easy-to-use. It suits wide range of users from new to those who are familiar.